ChemInform Abstract: Catalytic Asymmetric Conjugate Addition of Terminal Alkynes to β‐Trifluoromethyl α, β‐Enones. Issue 24 (2nd June 2014) - Sanz‐Marco, Amparo; Garcia‐Ortiz, Andrea; Blay, Gonzalo; Pedro, Jose R.
Abstract The first enantioselective conjugate alkynylation of β‐trifluoromethyl α, β‐enones (II) using terminal alkynes (I) and a taniaphos‐Cu(I) complex as catalyst is described.